Perturbation drives changing metapopulation dynamics in a top marine predator. Issue 1928 (10th June 2020) - Carroll, Emma L.; Hall, Ailsa; Olsen, Morten Tange; Onoufriou, Aubrie B.; Gaggiotti, Oscar E.; Russell, Debbie JF
Abstract : Metapopulation theory assumes a balance between local decays/extinctions and local growth/new colonisations. Here we investigate whether recent population declines across part of the UK harbour seal range represent normal metapopulation dynamics or are indicative of perturbations potentially threatening the metapopulation viability, using 20 years of population trends, location tracking data ( n = 380), and UK-wide, multi-generational population genetic data ( n = 269). First, we use microsatellite data to show that two genetic groups previously identified are distinct metapopulations: northern and southern. Then, we characterize the northern metapopulation dynamics in two different periods, before and after the start of regional declines (pre-/peri-perturbation). We identify source–sink dynamics across the northern metapopulation, with two putative source populations apparently supporting three likely sink populations, and a recent metapopulation-wide disruption of migration coincident with the perturbation. The northern metapopulation appears to be in decay, highlighting that changes in local populations can lead to radical alterations in the overall metapopulation's persistence and dynamics.